Penerapan Nesting terhadap Perubahan Saturasi Oksigenasi dan Frekuensi Nadi pada Bayi dengan Berat Badan Lahir Rendah di Ruang Perinatologi RSUD Batang - Sri Rahayu; Dwi Retnaningsih (Lembaga Pengembangan Kinerja Dosen, 2026)
Low Birth Weight (LBW) infants are among the leading causes of neonatal morbidity and mortality in Indonesia. This condition is associated with the immaturity of organ systems, including thermoregulation and respiratory function, making infants prone to stress, hypothermia, and oxygenation problems. One nursing intervention that helps improve physiological stability is the nesting technique, which positions the baby similarly to the intrauterine condition using soft rolled cloths as a “nest.” This case study aimed to determine the effect of nesting on oxygen saturation and pulse frequency changes in LBW infants in the perinatology room of RSUD Batang. The design used a descriptive case study with a nursing process approach involving 5 LBW infants who met inclusion criteria. The intervention was carried out by applying nesting for 30 minutes, then measuring oxygen saturation and pulse rate before and after the intervention using a pulse oximeter. The results showed an increase in oxygen saturation and changes in pulse rate after nesting. The mean oxygen saturation before intervention was 94%, increasing to 98% after three days of treatment. The average pulse rate increased from 130 beats/minute to 136 beats/minute, remaining within normal physiological limits (120–160 bpm). This indicates improved comfort and physiological stability due to the flexed position during nesting, which reduces stress and enhances oxygen efficiency. In conclusion, the nesting technique effectively improves oxygen saturation and stabilizes pulse rate in LBW infants. It is recommended as an evidence-based nursing practice for promoting comfort and physiological stability in premature or LBW infants in perinatology units.